Association between gestational bisphenol a exposure and maternofoetal outcomes: a cohort study in a single tertiary hospital in Klang Valley - Juliana Yusof; Sarah Zulkifli; Mohd Shahril Ahmad Saman; Danial Efendy Goon; Nurliana Abd Mutalib; Nur Izzaty Yusnazery; Izzuan Khirman Adnan; Siti Hamimah Sheikh Abdul Kadir (Penerbit Universiti Kebangsaan Malaysia, 2024)
A growing body of literature has documented the adverse effects of bisphenol A (BPA) exposure on pregnancy and birth outcomes. Regardless, how gestational BPA exposure affects mother-newborn pairs in Malaysia is yet to be explored. Hence, this study aimed to investigate urinary BPA levels of pregnant women living in Klang Valley and their associations with adverse obstetric and birth outcomes. This cross-sectional study involved pregnant women in their third trimester attending antenatal clinic in Hospital Al Sultan Abdullah (HASA), UiTM Puncak Alam, who planned to have their delivery in HASA. Information on maternal age, parity, education, household income, gestational age, and obstetric complications, such as Gestational Diabetes Mellitus (GDM), preeclampsia, preterm labour, and foetal growth restriction (FGR) were collected. Maternal urine samples were also obtained and evaluated using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Additionally, the neonatal outcomes including mode of delivery, gestational age, birth weight and need for NICU admission were documented. Our LC-MS/MS analysis showed that BPA was present in all the urine samples, with levels varying from 4.42 to 30.86 ng/mL. The median level was 15.96 ng/mL. Urinary BPA level has no significant correlation with gestational hypertension (GHTN), preterm labour and low birth weight babies. Babies who need NICU admission were born to mothers who exhibited significantly different urinary BPA levels compared to those whose babies were not admitted (p=0.049). Finding from this study suggestive of further investigation on level of gestational urinary BPA with NICU admission, ideally with a larger sample size to validate these results.